Fungal contamination of Azadi Teaching Hospital and Hevi Paediatric Hospital Environments, Duhok, Iraq - Shilan S. Saleem; Wasan M. Alnakshabandie; Asia A. M. Saadullah (Tikrit Journal of Pure Science)
This survey study was undertaken to find out the prevalence and distribution of fungi occupying the residential surfaces in Azadi Teaching Hospital and Hevi Paediatric Hospital in Duhok province, Iraq. Three hundred samples were collected from randomly selected areas in laboratories, wards, consultation rooms, operating theatres and hospital kitchen by swabs. These samples were cultured on two selective fungal media (PDA and SDA) and also samples from air were cultured on PDA in order to determine the genus or species of the agents in the samples. The results found microorganisms that were identified included forty eight isolates in addition to non identified yeasts and sterile mycelium also detected. From 300 samples collected from period January to May 2016, molds comprised 60% and yeasts comprised 40%. All fungal isolates were identified depending on the morphological and microscopic examinations as well as biochemical tests. The environmental contaminations in Azadi Teaching and Hevi Paediatric Hospitals with fungi (Aspergillus) were the highest fungal isolates whereas Candida sp. was the highest yeast isolate